John Coltrane: the work and its legacy - Whyton, Tony; Tackley, Catherine; Cotro, Vincent (Jazz Research Journal, 2009)
Welcome to the first of two special issues of the Jazz Research Journal focusing on the music and legacy of John Coltrane. 2007 witnessed several publications and events that commemorated the 40th anniversary of Coltrane’s death, each in their own way designed to examine the impact and influence of this iconic artist on jazz past and present.1 Today, the impact of Coltrane’s life and music can still be seen across literature, visual arts and performance, and a sizeable body of published work offers insights into the artist’s music, spirituality, politics and cultural influence. It is within this context that we felt that a themed issue would not only be timely, capturing some of the most recent insights into Coltrane’s music, but also of significant interest to our multi disciplinaryreadership. Featured articles in this issue were originally presented at the Colloque International John Coltrane, University of Tours, in November 2007. Following the event, the conference organizer and musicologist Vincent Cotro contacted the Jazz Research Journal to discuss the possibility of featuring papers which had been presented during the two-day event. Subsequently, several researchers were invited to expand their work and submit articles to the Jazz Research Journal for peer review. As Cotro states below, research sessions and panel discussions raised a number of critical issues that exceeded the initial boundaries of the colloquium. Contributors therefore had the opportunity to draw on the broader outcomes of the event in developing their work for publication. As a point of departure for our readers, Cotro has written the following contextual outline of the Colloque International John Coltrane alongside an introduction to the contributions to this issue.